Secondary Syphilis and Human Immunodeficiency Virus (HIV) Co-infection in Men Who Have Sex with Men (MSM) with Triple Doses Benzathine Penicillin G Treatment: A Case Report - sunarto, olivia awwalin; Suyoso, Sulaksanaswastho; Adhi Dharmasanti, Prasti (Faculty of Medicine, Universitas Airlangga, 2023)
Background: World Health Organization (WHO) reported that there are 6 million new cases of syphilis worldwide per year. The incidence of syphilis in Indonesia has increased over the past few years, particularly among men who have sex with men (MSM). Purpose: To report a case of secondary syphilis with Human Immunodeficiency Virus (HIV) coinfection in MSM, thereby increasing understanding of high-risk sexual behavior among MSM. Case: A 26-year-old man with a chief complaint of rashes on both palms, soles of the feet, and face. The rashes spread with no itching, heat, or pain, which occurred two weeks ago. The patient was diagnosed with HIV in 2019. Physical examination found multiple violaceus macules with clear boundaries, 0.5–1 cm in size, covered with scales. Venereal Disease Research Laboratory (VDRL) serology titer was 1:16 and Treponema Pallidum Haemagglutination Assay (TPHA) was 1:20.480. The recent CD4 count was 440 with an undetectable HIV RNA viral load. Benzathine penicillin G 2.4 million units was given intramuscularly 3 times at 1-week intervals. The patient experienced clinical improvement and decreased VDRL and TPHA titers. Discussion: Syphilis patients with or without HIV would have similar clinical symptoms. However, syphilis patients with HIV tend to have more extensive lesions. The treatment option with three doses of benzathine penicillin G is still very effective in cases of syphilis with HIV. Conclusion: Syphilis has a higher incidence in MSM patients with extensive clinical manifestations of skin lesions. It can be observed in syphilis patients with HIV; therefore, close monitoring is needed.